Effects of the combination of ω-3 PUFAs and proanthocyanidins on the gut microbiota of healthy rats. (July 2017) - Ramos-Romero, Sara; Hereu, Mercè; Molinar-Toribio, Eunice; Almajano, María Pilar; Méndez, Lucía; Medina, Isabel; Taltavull, Núria; Romeu, Marta; Nogués, Maria Rosa; Torres, Josep Lluís
Abstract: ω-3 Polyunsaturated fatty acids (PUFAs) reduce risk factors for cardiovascular diseases (CVD) and other pathologies that involve low-grade inflammation. They have recently been shown to exert complementary functional effects with proanthocyanidins. As the reduction of health-promoting gut bacteria such as lactobacilli and bifidobacteria has been linked to a number of alterations in the host, the aim of this study was to determine whether PUFAs and proanthocyanidins also cooperate in maintaining well-balanced microbiota. To this end, rats were supplemented for 6 months with eicosapentaenoic acid (EPA)/docosahexaenoic acid (DHA) 1:1 (16.6 g/kg feed); proanthocyanidin-rich grape seed extract (GSE, 0.8 g/kg feed); or both. Plasma adiponectin, cholesterol, and urine nitrites were measured. Gut bacterial subgroups were evaluated in fecal DNA by qRT-PCR. Short-chain fatty acids (SCFAs) were determined in feces by gas chromatography. Body and adipose tissue weights were found to be higher in the animals given ω-3 PUFAs, while their energy intake was lower. Plasma cholesterol was lower in ω-3 PUFA supplemented groups, while adiponectin and urine nitrites were higher. ω-3 PUFAs reduced the population of Lactobacillales and L. acidophilus after 6 months of supplementation. GSE significantly reduced L. plantarum and B. longum . The combination of ω-3 PUFAs and GSE maintained the health-promoting bacteria at levels similar to those of the control group. Acetic acid was increased by the ω-3 PUFA individual supplementation, while the combination with GSE kept this value similar to the control value. In conclusion, while individual supplementations with ω-3 PUFAs or GSE modify the populations of Lactobacillus, Bifidobacterium and microbial products (SCFAs), their combination maintains the standard proportions of these bacterial subgroups and their function while also providing the cardiovascular benefits of ω-3 PUFAs. Highlights: ω-3 PUFAs reduce the populations of gut Lactobacilliales and L. acidophilus . ω-3 PUFAs reduce the concentration of the microbial product acetic acid in feces. GSE reduces the populations of gut Lactobacillus plantarum and Bifidobacterium longum . ω-3 PUFAs promote weight gain and fat accumulation in healthy rats. Combined, ω-3 PUFAs and GSE maintain balanced gut bacteria and short-chain fatty acids. Graphical abstract: